General electronics - MEHELLOU Saïd (Université of eloued جامعة الوادي, 2024)
This course brings together all the essential elements of electro kinetics, passive quadrupoles, and diodes. It is structured into three chapters which deal with the fundamental notions of electrical circuits in continuous, sinusoidal and transient regimes then review the passive quadrupoles and ending with the study of diodes. The student will first discover, in a few pages, the essentials of the course where the essential knowledges are presented in a clear and precise manner. He will then be confronted with numerous exercises of varying difficulties. From simple applications of the course to more original cases, through very classic themes, the exercises and problems will allow the student to familiarize themselves with the basics of electricity, quadrupoles and diodes, then, by tackling more complex subjects, to acquire sufficient know-how to successfully solve any electronics problems. يجمع هذا المقرر بين جميع العناصر الأساسية للكهرباء الحركية، ورباعيات الاقطاب الخاملة ، وثنائيات الوصلة. وهو مقسم إلى ثلاثة فصول تتناول المفاهيم الأساسية للداراة الكهربائية في الأنظمة المستمرة والجيبية والمؤقتة ثم تستعرض ورباعيات الاقطاب الخاملة وتنتهي بدراسة ثنائيات الوصلة . سيكتشف الطالب أولاً، في بضع الصفحات، أساسيات المقرر حيث يتم تقديم المعارف الأساسية بطريقة واضحة ودقيقة ، ثم سيواجه العديد من التمارين ذات الصعوبات المتفاوتة ، من التطبيقات البسيطة للمقرر إلى الحالات الأكثر صعوبة، من خلال مواضيع كلاسيكية للغاية، ستسمح التمارين والمشكلات للطالب بالتعرف على أساسيات الكهرباء ورباعيات الاقطاب وثنائيات الوصلة ، ثم من خلال معالجة مواضيع أكثر تعقيدًا، لاكتساب المعرفة الكافية لحل معظم المشاكل إلكترونية بنجاح
(2nd year physics)
Learning Object
Keywords: electro kinetics; passive quadrupoles; diodes; electrical networks; continuous regime; variable regime; semi-conductors.; الكهرباء الحركية،; رباعيات الاقطاب الخاملة; ثنائيات الوصلة; الداراة الكهربائية،; النمط المتغير; أشباه الموصلات